The Effect of Exposure Time Per Layer on Dimensional Accuracy and Flexural Strength of 3D Printed Denture Bases - Sumitro, Sumitro; Putra, Kriswandy; Nasution, Nabila Rifani; Tambunan, Nur Aini Putri Nauli Br (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM)-based 3D printing technology is widely used in the manufacture of denture bases due to its precision and efficiency. However, the quality of the printed results is greatly influenced by printing parameters, especially the exposure time per layer that plays a role in the polymerization process of photopolymer resin. This study aims to analyze the effect of exposure time per layer on the dimensional accuracy and flexural strength of denture bases fabricated using Open System 3D Printing technology. This laboratory experimental study used a post-test only control group design. Denture bases were printed using an open system with exposure time variations of 4.5, 5, and 5.5 seconds, and compared with Close System 3D Printing and heat-polymerized acrylic resin (RAPP). Dimensional accuracy was measured in length, width, and height parameters, while flexural strength was tested using the three-point bending test method. Statistical analysis was performed using Welch's ANOVA test and Tukey's extended test (α = 0.05). The results showed that exposure time per layer had a significant effect on dimensional accuracy and flexural strength (p = 0.000). In the open system, the highest length accuracy value was obtained at an exposure time of 5.5 seconds (64.99 ± 0.07 mm), followed by 4.5 seconds (64.98 ± 0.09 mm) and 5 seconds (64.94 ± 0.05 mm). The highest flexural strength value in the open system was obtained at an exposure time of 4.5 seconds (68.90 ± 1.27 MPa), followed by 5.5 seconds (67.29 ± 1.49 MPa) and 5 seconds (66.08 ± 2.32 MPa). The closed system group showed the highest flexural strength value (90.61 ± 2.72 MPa), while RAPP was 73.76 ± 3.60 MPa. It was concluded that the exposure time setting per layer plays an important role in optimizing the dimensional accuracy and mechanical properties of 3D printed denture bases